Prognostic factors in radiotherapy of anaplastic thyroid carcinoma: a single center study over 31 years - Jacob, Julia; Vordermark, Dirk; Lorenz, Kerstin; Medenwald, Daniel (Radiation oncology (London, England), 2023)
Background Anaplastic thyroid carcinoma has a very poor prognosis. We analyzed the effect of surgery, radiotherapy and chemotherapy on survival time and side effects in patients with ATC. Methods We retrospectively analyzed all patients (n = 63) with histologically confirmed ATC who presented at our clinic between 1989 and 2020. We analyzed the survival with Kaplan–Meier curves and cox proportional hazard models and acute toxicities with logistic regression models. Results Out of 63 patients, 62 received radiotherapy, 74% underwent surgery and 24% received combined chemotherapy. A median radiation dose of 49 Gy (range 4–66 Gy) was applied. In 32% of the cases opposing-field technique was used, in 18% 3D-conformal, in 27% a combination of opposing field and 3D-conformal technique and 21% obtained IMRT (intensity modulated radiotherapy) or VMAT (volumetric modulated arc radiotherapy). Median overall survival (OS) was 6 months. We identified five predictive factors relevant for survival: absence of distant metastases at the time of diagnosis (OS 8 months), surgery (OS 9.8 months), resection status R0 (OS 14 months), radiation dose of 50 Gy or higher (OS 13 months) and multimodal therapy (surgery, radiotherapy and chemotherapy) with a median OS of 9.7 months. Conclusion In spite of the dismal outcome, longer survival can be achieved in some patients with ATC using surgery and radiotherapy with a high radiation dose. Compared to our previous study, there are no significant advantages in overall survival. Trial registration Retrospectively registered.